Factors associated with work accidents in fishermen - Entianopa Entianopa; Sugiarto Sugiarto; Yusfrini Desilva Asri (Riset Informasi Kesehatan, 2023)
Background Fishermen's work accidents are a problem of work safety in the world, including in Indonesia. Sometimes the weather is extreme, increasing the risk of accidents and death for fishermen. (Objective) The research objective was to determine the relationship between knowledge, attitudes, PPE, and machine availability tools for fishermen in Tanah Choose Village, Banyuasin District, Banyuasin Regency in 2022. Method: This research is a quantitative study with a cross-sectional design. This research method is interview and observation. The results of the survey were analyzed invariably and bivariately using the Chi-Square statistical test. Results 56.2% of respondents experienced work accidents, 20.8% of respondents had good knowledge, 52.1% of respondents with a positive attitude, 50% of respondents used complete PPE, and 33.3% of respondents used machine safety devices. Bivariant results show that there is no relationship between knowledge and work accidents (value = 0.614), there is no relationship between attitude and work accidents (p-value = 0.687), there is no relationship between PPE and work accidents (p-value = 1.000), there is no relationship between the availability of machine safety devices and work accidents (p-value = 1,000) Conclusion: It is hoped that fishermen will improve their attitude, use complete PPE when working, and use safety devices on every work machine and equipment.